The C/C Genotype of the C-1019G (rs6295) Polymorphism of the 5-HT1A Receptor Gene Is Associated with Lower Susceptibility to Depressive Symptoms in a Rural Population in Mexico - Margarita Hernandez-Mixteco; Olga Lidia Valenzuela; Cecilia Luz Balderas-Vazquez; Paola Castillo-Juárez; Sandra Rivera-Gutiérrez; Rocío Liliana García-Reyes; Gilberto Cornejo-Estudillo; Ricardo Jiovanni Soria-Herrera; Moises León-Juárez; Addy Cecilia Helguera-Repetto; Daniel Valencia-Trujillo; Victoria Campos-Peña; et al. (Neurology International)
Background: Depression is one of the most prevalent mental health disorders worldwide, affecting a significant proportion of the global population. Its etiology is complex and influenced by the interaction of environmental factors and genetic variations. In Mexico, it has been reported that 41.3% of the population exhibits depressive symptoms. Previous studies have suggested that susceptibility to depression may be associated with the C-1019G (rs6295) polymorphism in the serotonin 1A (5-HT1A) receptor gene. Objective: In this study, we aimed to evaluate the association between the C-1019G polymorphism and depressive symptoms in a rural Mexican population. Methods: Using polymerase chain reaction–restriction fragment length polymorphism (PCR-RFLP), we examined the effect of C-1019G on depression symptoms, as evaluated by the Beck Depression Inventory. Data were obtained from 83 volunteers; individuals with depressive symptoms and those with a healthy mood were compared. Results: The results showed that the homozygous C/C genotype was found significantly more frequently in the control group than in individuals with depressive symptoms, particularly among men, and is thus associated with a decreased risk of depressive symptomatology. Conclusions: The C/C genotype could protect against susceptibility to developing depressive symptoms in a rural population in Mexico.